KONSTITUSIONALITAS PASAL 12 HURUF G DAN PASAL 51 AYAT (1) HURUF G UNDANG-UNDANG NOMOR 8 TAHUN 2012 DIKAITKAN DENGAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 4/PUUVII/ 2009, PUTUSAN MAHKAMAH KONSTITUSI NOMOR 79/PUU-X/2012, DAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 42/PUU-XIII/2015 - Rika Yuli Handayani; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
According to Article 24C of the Constitution of 1945, especially the decisionof the Court judgment in the judicial review of Law is final and binding. But howif the rule of law is also unconstitutional by the Constitutional Court decisionrevived in the laws changed but still set the same thing by the legislator as Article12 letter g and Article 51 paragraph (1) letter g of Law Number 8 of 2012.Interestingly, when issuance Court decision number 42/PUU-XIII/2015 testarticle 7 letter g of Law Number 8 of 2015 which sounds identical to the norm ofarticle unconstitutional it, and startling in the verdict of the Constitutional Courtstates grant the petition for partially unconstitutional conditional as the ruling ofthe Constitutional Court ruling Number 4/PUU-VII/2009. Then how about thenorm clause that contained in Law Number 8 of 2012, is constitutional orunconstitutional, ever tested to the Court but the Court rejected it by its DecisionNumber 79/PUU-X/2012.The results of this study is that Article 12 letter g and Article 51 paragraph(1) letter g of Law Number 8 of 2012 is unconstitutional and the legalimplications after the Constitutional Court Decision Number 4/PUU-VII/2009,the Constitutional Court Decision Number 79/PUU-X/2012, and theConstitutional Court Decision Number 42/PUU-XIII/2015 is a legal ambiguitypolitical rights of former prisoners, the loss of mutatis mutandis ConstitutionalCourt ruling, does not contain provisions by ne bis in idem, and invalidates theerga omnes nature of the Constitutional Court. Supposedly Article 12 letter g andArticle 51 paragraph (1) letter g that automatically declared invalid and for theformer Act that the Parliament and the President, should be sincere to review alllegislation along relating to the voting rights of former prisoners from adapted tothe Constitutional Court's decision is final and have binding force, and the Courtmust remain consistent with previous decisions.Keywords : Constitutional Court Decision - Constitutional Court - JudicialReview - Law